Pengaruh Beban Kerja Stres Kerja dan Komunikasi Terhadap Semangat Kerja (Studi pada Karyawan PT Besi Baja Metalindo Mojokerto) - Azimatul Khabibah; Rahayu Rahayu; Kasnowo Kasnowo (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
A company is one of the types of business entities protected by law as the place where the production process of a good or service is used to meet the needs of society. To the company’s goals, it requires the contribution of good employees. Cultivating a high working spirit should be considered by the company’s managers as an obligation whose nature is constant. Especially with regard to the workload that can cause work stress, communication between employees that can lead to an increase or decrease in working spirit. The aim of this survey is to know the impact of workload, work stress, and communication on employee work spirit. This research population is the entire staff of PT Iron Steel Metalindo of Mojokerto district. The sample was 78 using saturated sampling techniques. Data analysis techniques use double linear regression analysis with the help of the SPSS 25 program. Research findings show that workload variables have a negative and significant influence on the work spirit, work stress has a negative, significant impact on the working spirit, and communication has a positive and significant effect on the job spirit.